Dampak Tambang La Oroya terhadap Degradasi Lingkungan dan Pelanggaran Hak Asasi Manusia - Fani, Guillermo Valles; Supit, Christina Nataysha; Kryzstov, Sean; Pattinussa, Jhon Maxwell Yosua (Universitas Pelita Harapan, 2024)
La Oroya Mining is an accurate example that environmental degradation and human rights violations can happen as a cause and effect. Mining in La Oroya Peru is very famous because it is one of Peru's largest sources of income and is its trademark. Meanwhile, this mining is also proof that Peru continues its imperialism. However, it cannot be denied that the effects of mining itself have had an impact on environmental degradation and human rights violations in local communities. This mining has caused worrying short-term and long-term impacts. In this paper, the authors and team try to analyze using qualitative methods through secondary data from journals. The aim is to find key factors that cause and impact this environmental degradation and human rights violation. The team authors also try to connect with three International Relations theories, which are realism, constructivism, and green political theory to look at it from three different points of view to find out the details. Further, the author also tries to trace what actions the Peruvian people have taken, the involvement of the IACHR in this problem as an international organization, the participation of NGOs, and how it continues. Furthermore, the role of the government will also be explored whether they help in solving this problem or make it worse and continue. Lastly, team authors try to propose effective solutions that can be implemented to help solve this environmental problem.